2020
DOI: 10.1002/jia2.25574
|View full text |Cite
|
Sign up to set email alerts
|

Rapid antiretroviral initiation among Thai youth living with HIV in the National AIDS programme in the era of treatment at any CD4 cell count: a national registry database study

Abstract: Introduction The process indicators of ending the HIV epidemic include 90% of people living with HIV receiving antiretroviral therapy (ART). The population of youth, however, has less access to healthcare. We assessed ART initiation and attrition outcomes of the HIV continuum from HIV diagnosis to ART initiation in youth living with HIV (YLHIV) and factors associated with ART initiation. Methods We studied YLHIV aged 15 to 24 years who were registered on the National AIDS Program (NAP) from January 2008 to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…Policy changes regarding rapid ART initiation led to decreased mortality rates and increased retention in care, similar to those in our study [29, 30]. YLHIV starting rapid ART had the lowest mortality rates, consistent with results from randomized control trials and cohort studies [27, 31]. Rapid ART initiation also accelerated viral suppression rates.…”
Section: Discussionsupporting
confidence: 87%
“…Policy changes regarding rapid ART initiation led to decreased mortality rates and increased retention in care, similar to those in our study [29, 30]. YLHIV starting rapid ART had the lowest mortality rates, consistent with results from randomized control trials and cohort studies [27, 31]. Rapid ART initiation also accelerated viral suppression rates.…”
Section: Discussionsupporting
confidence: 87%
“…Observational studies from the Netherlands, South Korea, Thailand and New York City also reported a significant decrease in time from HIV diagnosis to treatment initiation in the 2012 to 2015 period, [38][39][40][41] when international guidelines began to recommend rapid ART initiation independent of CD4 count. [42][43][44][45][46] By 2015, however, 75% of people living with HIV in BC initiated ART within 2 months of their diagnosis, compared with 6 months, as noted in the other observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45][46] By 2015, however, 75% of people living with HIV in BC initiated ART within 2 months of their diagnosis, compared with 6 months, as noted in the other observational studies. [38][39][40][41] Although the independent impact of STOP in accelerating time from HIV diagnosis to treatment in BC was evident, the full public benefit of early ART to reduce transmission risk requires a decline in another, more complex, time component, namely time from infection to diagnosis. Delayed HIV diagnosis has previously been observed in 1 in 7 people living with HIV in BC, particularly those who were older, were heterosexual, had ever injected drugs and resided in the Northern health authority.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of rapid ART initiation (within 1 month of HIV diagnosis) increased significantly in the second time period compared with the first (52% vs 27%, p <0.001). The cumulative incidence of loss to follow‐up or death prior to ART initiation was also reduced between the two periods (3.8% [95% CI 3.6–4.1] vs 1.9% [95% CI 1.8–2.1]) [25]. A study from an HIV/sexually transmitted infection (STI) testing centre in Bangkok, Thailand, found high numbers of people living with HIV who were eligible and high rates of acceptability of same‐day ART initiation and that it was feasible and safe without immune reconstitution inflammatory syndrome.…”
Section: Evidence For the Benefits Of Rapid/same‐day Art Initiationmentioning
confidence: 99%
“…Many countries in the Asia-Pacific region have already implemented or are moving towards implementation of rapid or same-day ART initiation [24,25]. Table 1 outlines key recommendations for rapid ART initiation from guidelines from the USA, Europe, and countries in the Asia-Pacific region (Table 1).…”
Section: Country/ Guidelinementioning
confidence: 99%